Intracellular Competitions Reveal Determinants of Plasmid Evolutionary Success - Hülter, Nils F.; Wein, Tanita; Effe, Johannes; Garoña, Ana; Dagan, Tal (Frontiers in Microbiology, 2020)
Plasmids are autonomously replicating genetic elements that are ubiquitous in all taxa and habitats where they constitute an integral part of microbial genomes. The stable inheritance of plasmids depends on their segregation during cell division and their long-term persistence in a host population is thought to largely depend on their impact on the host fitness. Nonetheless, many plasmids found in nature are lacking a clear trait that is advantageous to their host; the determinants of plasmid evolutionary success in the absence of plasmid benefit to the host remain understudied. Here we show that stable plasmid inheritance is an important determinant of plasmid evolutionary success. Borrowing terminology from evolutionary biology of cellular living forms, we hypothesize that Darwinian fitness is key for the plasmid evolutionary success. Performing intracellular plasmid competitions between non-mobile plasmids enables us to compare the evolutionary success of plasmid genotypes within the host, i.e., the plasmid fitness. Intracellular head-to-head competitions between stable and unstable variants of the same model plasmid revealed that the stable plasmid variant has a higher fitness in comparison to the unstable plasmid. Preemptive plasmid competitions reveal that plasmid fitness may depend on the order of plasmid arrival in the host. Competitions between plasmids characterized by similar stability of inheritance reveal plasmid fitness differences depending on the plasmid-encoded trait. Our results further reveal that competing plasmids can be maintained in coexistence following plasmid fusions that maintain unstable plasmid variants over time. Plasmids are not only useful accessory genetic elements to their host but they are also evolving and replicating entities, similarly to cellular living forms. There is a clear link between plasmid genetics and plasmid evolutionary success – hence plasmids are evolving entities whose fitness is quantifiable.